2008
DOI: 10.1103/physrevlett.100.097401
|View full text |Cite
|
Sign up to set email alerts
|

Direct Observation of Dark Excitons in Micelle-Wrapped Single-Wall Carbon Nanotubes

Abstract: We have performed electroabsorption spectroscopy on micelle-wrapped single-wall carbon nanotubes. In semiconducting nanotubes, many oscillating structures composed of the increase and decrease of absorption are observed in the spectra in the region of the first and second absorption bands, E11 and E22. The spectral shape is reproduced mainly by the second-derivative curve of the absorption spectrum, which indicates the presence of nearly degenerate bright and dark excitonic states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…Fig. 4 shows the Im w (3) /a spectra in the E 11 transition region with the resonant excitation of the E 22 transition (1.92 eV) in the (7,6) tubes. Although this photon energy (1.92 eV) corresponds to the E 22 transition energies of both the (7,5) and (7,6) tubes, the E 11 transition energy of the (7,6) tube (1.105 eV) is well separated from that of the (7,5) tube (1.210 eV).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Fig. 4 shows the Im w (3) /a spectra in the E 11 transition region with the resonant excitation of the E 22 transition (1.92 eV) in the (7,6) tubes. Although this photon energy (1.92 eV) corresponds to the E 22 transition energies of both the (7,5) and (7,6) tubes, the E 11 transition energy of the (7,6) tube (1.105 eV) is well separated from that of the (7,5) tube (1.210 eV).…”
Section: Resultsmentioning
confidence: 98%
“…The exciton effects in 1D systems result in large thirdorder nonlinear optical responses in resonance regions of fundamental optical transitions. In isolated single-walled carbon nanotubes (SWNTs) sharp-peak structures due to 1D excitons have been observed in absorption spectra [5][6][7], and at these peaks thirdorder nonlinear susceptibilities w (3) have shown the strong resonance enhancement [8][9][10]. Moreover, we have reported that the figure of merit Im w (3) /a (a: absorption coefficient) strongly depends on the diameter D (D 6 ) [9].…”
Section: Introductionmentioning
confidence: 97%
“…Figure 2 shows the excitation spectrum of Im (3) / . When the excitation photon energy approaches to the E 22 transition energy of the (8,4) increases. In addition, we observe an additional peak at 2.3 eV which is ~0.2 eV above the E 22 transition energy.…”
Section: Resultsmentioning
confidence: 99%
“…Third-order optical nonlinearities in single-walled carbon nanotubes (SWNTs) are strongly enhanced because of van Hove singularities of the density of states and exciton effects which are characteristic of quasi-one-dimensional systems (1D) [1][2][3][4]. The chiral vector indices (n,m) that correspond to a specific chiral angle and a diameter determine various optical properties of SWNTs.…”
Section: Introductionmentioning
confidence: 99%
“…The absence of Franz-Keldysh oscillations in EA spectra of nanotubes was used as evidence of the excitonic nature of the photoexcitations in SWNTs [7][8][9]. Furthermore, EA spectra have provided a quantitative estimate of exciton polarizability and size in individual species, evidence for charge trapping in SWNT bundles, and evidence for the existence of low-energy "dark" excitons in order to explain the low photoluminescence quantum efficiency in SWNTs [10][11][12].…”
Section: Introductionmentioning
confidence: 99%